003 Systemic inflammation, erythrocyte fragility and multiple sclerosis. Issue 6 (27th May 2022) - Stuart, Charlotte M; Howard, Sarah; Chouhan, Joe; Varatharaj, Aravinthan; Teeling, Jessica L; Galea, Ian
Abstract : In an unbiased proteomic assay, extracellular haemoglobin was the only serum protein which correlated with brain atrophy in secondary progressive MS. Increased erythrocyte osmotic fragility is reported in individuals with relapsing remitting multiple sclerosis (RRMS) versus control individuals and in active versus quiescent RRMS. Erythrocyte fragility has not been measured in progressive MS patients. Here we measure erythrocyte osmotic fragility in individuals with progressive MS versus control individuals. In a murine experimental model of systemic infection, we prove that systemic inflammation causes erythrocyte osmotic fragility. In summary, it is possible that extracellular hae- moglobin released during systemic infections contributes to MS pathology by entering the brain through a leaky blood-brain barrier. c.stuart@soton.ac.uk